Symptoms of infectious diseases in HIV-positive travellers: A prospective study with exposure-matched controls. Issue 29 (May 2019) - Suryapranata, Franciska; Boyd, Anders; Grobusch, Martin P.; Prins, Maria; Sonder, Gerard
Abstract: Background: Recently, the number of HIV-infected travellers to (sub)tropical areas has increased substantially. In the Netherlands, HIV-positive travellers with CD4-cells of <500/mm 3 are advised to carry stand-by antibiotic treatment against travellers' diarrhoea. Our aim was to determine whether HIV infection is associated with travel-related symptomatic diseases. Methods: A prospective study was performed among HIV-infected travellers and age-matched HIV-uninfected travel companions serving as controls, attending two travel clinics in Amsterdam. Participants filled out daily questionnaires before, during, and after their trip. Results: Overall, 52 pairs were included. All participants were male, and 91.3% were born in a Western country. Prevalence of travel-related diarrhoea was 50% among HIV-positive travellers and 40% among controls. No significant differences were observed for incident travel-related diarrhoea (incidence rate ratio = 1.60, 95%CI = 0.79–3.27) or duration of symptoms (odds ratio = 1.49, 95%CI = 0.65–3.45). There were no significant differences in symptom incidence or duration for travel-related vomiting, cough, rhinitis, pruritus, fatigue, or nausea. Only 6.3% of HIV-positive travellers with CD4-cells of <500/mm 3 and diarrhoea used their stand-by antibiotic treatment as recommended. Conclusion: Travel-related symptoms were not significantly more frequent or longer lasting among HIV-infected travellers compared to controls. Most HIV-infected travellers with CD4-cells of <500/mm 3 and diarrhoea did not take stand-by antibiotic treatment. These results may question the need for routine prescription of stand-by antibiotics among this specific risk group. Further research, especially among HIV infected VFR travellers and in larger study groups is needed.